Pengaruh Gaji, Work Overload, Dan Stres Kerja Terhadap Kepuasan Kerja Karyawan (Studi Pada Karyawan Sandang Ayu Department Store Pasuruan) - Hilda Putri Dwi Oktaviani; Muhammad Agus Salim; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to examine and explain the effect of salary, work overload and work stress simultaneously on job satisfaction of Sandang Ayu Pasuruan employees. The population in this study were all employees of Sandang Ayu Department Store Pasuruan, totaling 160 people. The technique of determining the sample using the slovin formula with the level of validity of a sample, then a maximum Margin of error of 10% is used. So, the sample in this study amounted to 62 employees. While the analytical tool used is Multiple Linear Regression using SPSS. The results of this study simultaneously salary, work overload and work stress have a significant effect on employee job satisfaction. The salary variable has a significant effect on employee job satisfaction. Work overload also gives the same results in the form of a significant effect between work overload variables on employee job satisfaction. It is also known that the variable of work stress has a significant effect on employee job satisfaction. Keywords: Salary, Work Overload, Work Stress, And Employee Job Satisfaction